Penerapan Black Box Testing Menggunakan Teknik Equivalence Partitioning pada Sistem Informasi Akademik (SIAKAD) Kampus UKRI - Destyan Fadillah Akbar; Leo Restu Septian Rhaka Nugraha; Prayogi Nur Aldi; Alif Prambudi Fadillah Akbar; Farid Zia Ulhaq; Subhanjaya Angga Atmaja (Journal on Pustaka Cendekia Informatika, 2025)
Digital transformation in higher education demands the reliability of academic information systems in supporting administrative and academic processes for students in an independent and efficient manner. The Academic Information System (SIAKAD) serves as a vital tool in managing student academic data, including login, payment, attendance, document printing, as well as leave applications and account data changes. This study aims to evaluate the functionality of the SIAKAD at Universitas Kebangsaan Republik Indonesia (UKRI) from the students’ perspective using the black box testing method with the Equivalence Partitioning technique. The study employs a descriptive qualitative approach, with data collection techniques including direct observation and documentation of system testing results based on valid and invalid inputs. The testing results indicate that all core features function as expected; input validation, notifications, and user interaction flows operate properly and consistently. These findings contribute to the development of web- based academic systems, particularly in the application of efficient testing techniques focused on user experience. This study also opens avenues for further exploration into system performance, security, and testing for other user roles in the future.